Sleep Quality Among Informal Caregivers During the COVID-19 Pandemic: A Cross-Sectional Study. (1st January 2022) - Greaney, Mary L.; Kunicki, Zachary J.; Drohan, Meghan M.; Nash, Caitlin C.; Cohen, Steven A.
Sleep is an integral component of health. The impact of the COVID-19 pandemic on sleep quality among informal caregivers, individuals who provide unpaid care or assistance to family members or friends, assisting older adults is not well understood. Therefore, informal caregivers in the United States providing care for individuals aged 50+ were recruited via Amazon's Mechanical Turk, an online platform for enrolling study participants into social and behavioral science research, to complete an online survey. The sample of informal caregivers ( n = 835) was 69% male and 55% non-Hispanic. Multivariable linear regression models were constructed to assess the associations between sleep disturbance scores (SDS) and sleep-related impairment scores (SIS) and caregiving-related measures (hours caregiving/week, length of time spent caregiving, and caregiver burden), demographics, and region of the United States. The analysis determined that Black (β = 2.6, 95% CI [−4.3, −0.9]) and Asian informal caregivers (β = −1.8, 95% CI [−3.4, −0.3]) had lower mean SIS than White caregivers, the referent group. In addition, increasing caregiver burden was associated with increased SDS (β = 0.8, 95% CI [0.6, 1.0]) and SIS (β = 1.3, 95% CI [0.7, 1.6]). In conclusion, higher caregiver burden was associated with higher SIS and SDS, suggesting that informal caregivers' sleep should be assessed, and when needed interventions should be offered.